Geochronological and paleoenvironmental reconstruction of colluvial deposits in a cuesta landscape in south-eastern Brazil - de Godoi Pinton, Leandro; Lupinacci, Cenira Maria [UNESP] (Wiley, 2022)
The classic models of cuesta evolution in south-eastern Brazil have temporal gaps in their denudation chronology. Here, we analyzed the colluvial deposits located on the rim of the Serra Geral escarpments in the Paraná Basin to propose a model with an absolute age range of minor landform evolution within this cuesta morphology. Correlation of the optically stimulated luminescence ages with the regional paleoclimatic conditions demonstrates that the successive phases of colluviation reflect either short-term intervals of variability in moisture availability or dry periods in the Holocene. The potential effects of other contributing factors (vegetation changes, local geomorphic settings and human activity) add complexity to the denudation responsible for the development of the investigated geomorphic chronosequences. The proposed model consists of five stages of hillslope sediment remobilization that were responsible for further remodeling of the minor vertical steps during the following chronological distribution: (i) 9.13 ± 1.2–7.09 ± 0.96 ka; (ii) 5.66 ± 0.86–4.5 ± 0.75 ka; (iii) 3.94 ± 0.605–3.45 ± 0.6 ka; (iv) 2.66 ± 0.315–2.3 ± 0.4 ka; and (v) after 1960 to the present day.
Keywords: colluvium; cuesta landscape; optically stimulated luminescence (OSL); paleoclimate; Quaternary geomorphology